Long-run price elasticities of demand for credit: Evidence from a countrywide field experiment in Mexico - Dean Karlan; Jonathan Zinman (Yale University, Economic Growth Center, 2013)
The long-run price elasticity of demand for credit is a key parameter for intertemporal modeling, policy levers, and lending practice. We use randomized interest rates, offered across 80 regions by Mexicos largest microlender, to identify a 29-month dollars-borrowed elasticity of -1.9. This elasticity increases from -1.1 in year one to -2.9 in year three. The number of borrowers is also elastic. Credit bureau data does not show evidence of crowd-out. Competitors do not respond by reducing rates, perhaps because Compartamos profits are unchanged. The results are consistent with multiple equilibria in loan pricing.
Keywords: E43; G21; O11; O12; 330; microcredi; interest rates; interest rate policy; interest rate elasticities; Zins; Kredit; Preiselastizität; Mikrofinanzierung; Mexiko